Analisis Indeks Pembangunan Manusia (IPM) Kabupaten/Kota di Provinsi Maluku Utara Menggunakan Indeks Geary C Berdasarkan Resampling Estimasi Densitas Kernel - Fetriks Theo Sarita; Adi Setiawan; Hanna Arini Parhusip (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
In this study, it is discussed the Regency/City Human Development Index (HDI) in North Maluku Province to determine the spatial influence of HDI. The data used are Regency/City HDI in North Maluku Province from 2013 to 2017. Furthermore, spatial autocorrelation test with Geary C index is used based on resampling by using Estimated Kernel Density. The test is done to determine whether the Regency/City HDI affects the neighboring Regency/City HDI. Based on the results of optimal bandwidth usage (hopt) with a repetition of 10000 times it is obtained p-value 0.0318, 0.0272, 0.0282, 0.0262 and 0.0258, respectively from 2013 to 2017. Thus, there is a spatial between Regencies/Cities in North Maluku Province from 2013 to 2017. In other words, if the HDI in a Regency/City is high then the neighbouring Regency/City HDI tends to be high, and vice versa.